Pacific sailfish (Istiophorus platypterus) in the Eastern Pacific Ocean, association with ocean currents and seasonal effects of upwelling using real-time Argos locations - Clyde-Brockway, Chelsea E.; Patel, Samir Harshad; Blanco, Gabriela; Friederichk, Samuel J.; Morreale, Stephen; Paladino, Frank V. (Frontiers in Fish Science, 2025)
Pacific sailfish (Istiophorus platypterus) are the most abundant marlin in Central American waters and are a species of socioeconomic and ecological importance with sport fishing generating millions of dollars (USD) and thousands of jobs each year. Concurrently, sailfish are caught as bycatch in purse seine and longline fishing gear potentially threatening the stability of the population and sportfishing community. In this study, Wildlife Computers Mk10 satellite transmitters were deployed on sailfish (n = 6) which relayed real time Argos satellite locations and post-release light-derived geolocation positional estimates. The two location recording methods produced similar tracking intervals—deployment date until the final location date—(Argos: 33.0 ± 13.5 d; GPE: 32.0 ± 11.2 d), and detection days—number of days the transmitter recorded a location—(Argos: 7.8 ± 6.0 d; GPE: 12.3 ± 8.5 d). In total, displacement distances from initial tagging to final (Argos) location ranged from 339.92 to 985.59 km and crossed 6 different Exclusive Economic Zones. During migrating, sailfish exhibited alternating with-current and against-current movements, a pattern that was consistent in both the upwelling and non-upwelling seasons. Despite the known fluctuations associated with seasonal upwelling in the eastern Pacific, sailfish experienced relatively stable microenvironments with average temperature variability remaining within 2°C. Behavioral modification to achieve this consistency could be through depth use (48 ± 28 m vs. 37 ± 47 m), though this mechanism alone seems unlikely to fully explain their ability to mitigate environmental dynamics. Further research is needed to understand the mechanisms underlying these behavioral adaptations and the ecological factors that contribute to sailfish resilience. Additionally, strengthened protection measures are critical to ensure the conservation of sailfish in Costa Rica, including elimination of all commercial sale.